COGNITIVE DOMAIN OF REVISED BLOOM TAXONOMY IN ENGLISH STUDENT BOOK - Saputra, Herdiansyah Tri; Pujiati, Hanip (Journal of English Language and Literature Teaching, 2023)
The presence of Cognitive Domains in the instructions of learning activities in the textbook is important, especially for developing students’ thinking skills. This research aimed to investigate the cognitive process dimensions and knowledge dimension of Bloom’s Revised Taxonomy represented in all of the instructions of learning activities provided in the “English in Mind Starter Second Edition (Student’s Book) Special Edition” written by Herbet puchta and Jeff Stranks. This research is qualitative descriptive with content analysis design. To collect data, the table adapted from Anderson and Krathwohl’s taxonomy table are used. The study revealed that: (1) All levels in Cognitive Process Dimension of BRT are existed in instructions with the most used level of Cognitive Process Dimension was Remember, with 233 times of occurrence (50%), and (2) Three of Four Knowledge Dimension are existed in the instructions, the Factual Knowledge was the most dominantly distributed 247 times with 53% of percentage, while Metacognitive Knowledge is absent. The findings revealed that shows how the instructions of learning activities in this textbook put more emphasis on LOTS rather than HOTS. Based on the findings, the researcher suggested that textbook writers and teachers need to provide more balanced distribution of Cognitive Domain and focusing on higher level thinking rather than lower order level thinking.